2019
DOI: 10.1002/lary.28456
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Origin of the Auricula Revisited

Abstract: Objectives/Hypothesis Congenital auricular anomalies are common. Additionally, the auricle plays an important role in the staging of human embryos. However, little is known about the embryological development of the auricle. The most commonly reproduced developmental theory by His (1885) describes six hillocks; three on the first and three on the second pharyngeal arch. The aim of this study was to assess the validity of this theory by modern techniques and to expand the knowledge of the embryological developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…To analyze morphogenesis in early auricular elastic cartilage, we observed the auricular hillocks, which differentiate into auricular cartilage, in E11.5 mouse embryos. 21 23 Morphological characteristics, such as a 200–300 μm diameter, round shape, and adjacent positioning, were moderately consistent with those of human auricular hillocks ( Figure 1(b) ). 22 Immunohistochemistry analysis indicated that the auricular hillocks were positive for type I collagen (a broad mesenchymal marker) and SOX9 (a craniofacial chondrogenic and mesenchymal condensation marker) 24 , 25 and negative for type II collagen (a chondrogenic marker).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…To analyze morphogenesis in early auricular elastic cartilage, we observed the auricular hillocks, which differentiate into auricular cartilage, in E11.5 mouse embryos. 21 23 Morphological characteristics, such as a 200–300 μm diameter, round shape, and adjacent positioning, were moderately consistent with those of human auricular hillocks ( Figure 1(b) ). 22 Immunohistochemistry analysis indicated that the auricular hillocks were positive for type I collagen (a broad mesenchymal marker) and SOX9 (a craniofacial chondrogenic and mesenchymal condensation marker) 24 , 25 and negative for type II collagen (a chondrogenic marker).…”
Section: Resultssupporting
confidence: 57%
“…[21][22][23] Morphological characteristics, such as a 200-300 μm diameter, round shape, and adjacent positioning, were moderately consistent with those of human auricular hillocks (Figure 1(b)). 22 Immunohistochemistry analysis indicated that the auricular hillocks were positive for type I collagen (a broad mesenchymal marker) and SOX9 (a craniofacial chondrogenic and mesenchymal condensation marker) 24,25 and negative for type II collagen (a chondrogenic marker). These results were consistent with previous reports that the auricular hillocks are the origin of auricular cartilage and that they exhibit a mesenchymal character at this stage (Figure 1(c), Supplemental Video 1).…”
Section: Auricular Hillocks In Mice Embryosmentioning
confidence: 74%
See 2 more Smart Citations
“…The ear is uniquely innervated by the branches of the trigeminal, facial, glossopharyngeal, and vagal cranial nerves and the superficial cervical plexus due to its embryological origin [21, 22]. The nuclei of these cranial nerves are located in the brainstem and closely connected to a number of structures, including the tractus solitaries and structures involved in the limbic system such as the thalamus and hypothalamus, amygdala, and rostral ventral medulla [13].…”
Section: Discussionmentioning
confidence: 99%